Study success at the Turku University of Applied Sciences : Comparison between students of path studies background and joint-application background and comparison between different study fields - Roos, Emmi (My University, 2021)
This thesis examines the study success of different student groups of Turku University of Applied Sciences. Study success is measured in this research with the amount of credits and weighted grade point average. Two research questions are presented to explore the phenomenon, first one concerns the possible difference in the study success of path students and students with joint-application background. The second research question looks at the differences between the study success of four different study fields. The data has been collected from the groups of students starting their studies in the Turku University of applied sciences in four semesters: autumn 2017, spring 2018, autumn 2018, and spring 2019. Theoretical background of the thesis is based on the previous studies on the factors which affect study success in higher education. Results of this study show that there are no statistically significant differences between the study success of students with path studies background in comparison with students with joint application background. Nevertheless, when looking at the differences between different study fields, statistically significant differences can be found. Results provide new knowledge about the study success of the students studying in the universities of applied sciences. Results show that the way of access to universities of applied sciences does not seem to relevant for the later success in studies and that instead, other factors, such as study field, explain the differences in study success.
Keywords: study success, university of applied sciences, path studies, study field, student selection, lifelong learning